SURVEY ON MEDICAL, DEMOGRAPHIC, AND SOCIOECONOMIC INDICATORS IN TAJIKISTAN - R.A. NAIMOV (Паёми Сино)
Objective: An evaluation of various medical and demographic indicators and their impact on the development of Tajikistan.